Polemik Perkembangan Manusia Antara Baka dengan ‎Persekitaran Menurut Barat dan Perspektif Islam ‎: The Polemic of Human Development Between Nature and ‎Nurture According to Western and Islamic Perspectives - Mansor, Nur Azwani; Abdullah, Mohd Azhar (RABBANICA - Journal of Revealed Knowledge, 2025)
This study discusses the schools of thought related to the perspectives of heredity and environment in human growth and development, drawing on both Western ideologies and Islamic perspectives. Human growth and development are influenced by two primary factors: heredity, or genetic factors (nature), and environmental or educational factors (nurture). Before the terms heredity and environment were introduced, there were already schools of thought supporting both perspectives, and this debate has existed since ancient times. However, to this day, Western scholars remain divided in their opinions and beliefs about which influence dominates human growth and development. The methodology of this study employs content analysis of data obtained from books and documents on the history of schools of thought related to heredity and environment. The data focuses on factors influencing human growth and development by examining the relevant schools of thought. The findings of the study indicate that the schools of Nativism and Naturalism support the heredity perspective, whereas the school of Empiricism supports the environmental perspective. This contradiction and diversity of beliefs have led to the emergence of a new school of thought that combines heredity and environment, known as the school of Convergence. In essence, growth and development involve several aspects, including physical, emotional, mental, linguistic, social, personality, and moral dimensions, which are influenced by both biological and environmental factors. This is because these two factors complement each other and are closely interconnected with the level of human development. Kajian ini membincangkan tentang aliran-aliran yang berkaitan dengan perspektif baka dan persekitaran dalam pertumbuhan dan perkembangan manusia berdasarkan ideologi Barat dan Perspektif Islam. Manusia tumbuh dan berkembang berdasarkan dua pengaruh dominan iaitu faktor baka atau genetik (nature) dan faktor persekitaran dan pendidikan (nurture). Sebelum istilah baka dan persekitaran diperkenalkan, telah wujud aliran-aliran yang menyokong kedua-dua perspektif ini dan percanggahan tersebut telah wujud sejak dahulu lagi. Walau bagaimanapun, sehingga kini ahli-ahli sarjana Barat masih lagi bercanggah pendapat dan kepercayaan tentang pengaruh yang mana paling mendominasi dalam pertumbuhan dan perkembangan manusia. Metodologi penulisan ini menggunakan kaedah analisis kandungan terhadap data yang diperolehi dari buku dan dokumen tentang sejarah aliran-aliran yang berkaitan dengan baka dan persekitaran. Data yang diperolehi adalah memfokuskan kepada faktor-faktor yang mempengaruhi pertumbuhan dan perkembangan manusia dengan meneliti aliran-aliran berkaitan. Hasil kajian menunjukkan aliran Nativisme dan Naturalisme menyokong perspektif baka. Manakala aliran Empirisisme menyokong perspektif persekitaran. Percanggahan dan kepercayaan tersebut telah mewujudkan aliran baru yang menghasilkan percantuman kedua-dua baka dan persekitaran iaitu aliran konvergensi. Hakikatnya pertumbuhan dan perkembangan melibatkan beberapa aspek seperti fizikal, emosi, mental, bahasa, sosial, keperibadian dan moral dipengaruhi oleh kedua-dua faktor biologi dan persekitaran. Ini kerana kedua-dua faktor ini adalah saling melengkapi dan berkait rapat dengan tahap perkembangan manusia.